Human sectional anatomy : atlas of body sections, CT and MRI images / Harold Ellis, Bari M. Logan, Adrian K. Dixon, David J. Bowden - Ellis, Harold
First published in 1991, Human Sectional Anatomy set new standards for the quality of cadaver sections and accompanying radiological images. Now in its fourth edition, this unsurpassed quality remains and is further enhanced by the addition of new material.